OBSERVACIONES SOBRE LA FLORA Y VEGETACION DE DOS TURBERAS EN LA REGION DE AISEN, PATAGONIA CHILENA OBSERVATIONS ABOUT FLORA AND VEGETATION OF TWO PEATBOGS IN AISEN REGION, CHILEAN PATAGONIA - Ernesto Teneb (Universidad de Concepción, 2008)
We report results of flora and vegetation in two of Sphagnum peatbogs in the Aisén Region.